MEMAHAMI IMPLIKASI OPEN BANKING TERHADAP PRIVASI KONSUMEN DAN PERLINDUNGAN DATA DI INDUSTRI FINTECH - Sriyono Sriyono; Sindy Diva Maretha; Anintya Kurnia Devi (Ensiklopedia of Journal, 2023)
This study examines how the literature review of the influence of good corporate governance on earnings management. implications of Open Banking for consumer privacy and data protection in the fintech industry. The research used by researchers is Literature Review with data obtained from journals and research articles and other data sources. In this study, the results obtained are that Open Banking provides access to various types of customer data, including account information, transaction data, and payment initiation. This data can be used to create new financial products and services that can benefit consumers. Open Banking provides access to various types of customer data, including account information, transaction data, and payment initiation. This data can be used to create new financial products and services that can benefit consumers. Open Banking encourages innovation and can increase financial inclusion. However, it also presents challenges, such as data security and privacy risks and a lack of standardization. Open Banking is an evolving concept that is likely to have a significant impact on the financial industry. Fintech companies, traditional banks, and regulators all have a role to play in promoting Open Banking and ensuring its continued success.Keywords: Open Banking, Protection, Data Privacy.